One-pot synthesis of raspberry-like mesoporous silica nanospheres - Liu, Ting; Liu, Lihong; Gu, W.; Liu, J.; Liu, Shaomin (American Scientific Publishers, 2018)
Mesoporous materials with hierarchical morphologies have recently gained attention due to their structural versatility for various applications including catalysis, adsorption, energy storage and nanomedicine. However, it is still desirable for facilely controllable synthesis of mesoporous particles with tunable surface properties and oriented hierarchical structures. Here, we report a one-pot synthesis method for raspberry-like mesoporous silica nanospheres with 2 nm hollow silica nanoparticles doped on the surface. We iden tify that the control over the concentration of cationic surfactant and silica precursor can be used to control the multiple morphological evolutions of mesoporous silica nanoparticles. This control enables the fabrication of a diverse library of multi-compartment mesoporous silicas networks consist of mesoporous silica nanospheres connecting with mesoporous silica branches. The synthesis method would enable to synthesize hierarchical mesoporous silicas with complex architecture and different pore environments for the potential application in catalysis and nanomedicine.